Tinjauan Hukum Mengenai Tenaga Kerja Indonesia (TKI) Illegal yang Terjadi di Indonesia - Setyarini, Astri Dewi; Prasetyo, Handoyo (Media Hukum Indonesia (MHI), 2024)
Problems related to Indonesian Workers (TKI) stem from the ineffective management of companies that distribute TKI. The lack of education of prospective migrant workers makes them vulnerable to fraud. Low understanding of the rules for working abroad is also a serious problem. Government protection for migrant workers is regulated in law, but there are still shortcomings in its implementation. Solutions to overcome this problem include improving recruitment, providing training to prospective migrant workers, and making agreements with the destination countries for migrant workers. Legal protection for migrant workers needs to be strengthened, including for domestic helpers who are vulnerable to exploitation. Current labor laws do not provide adequate protection for them. Improvements in legal protection for migrant workers and domestic helpers need to be made both domestically and abroad.